1989
DOI: 10.1038/clpt.1989.180
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine metabolism in human liver microsomes by cytochrome P450IIIA4

Abstract: The metabolism of lidocaine to its major metabolite monoethylglycinexylidide (MEGX) was studied in human liver microsomes of 13 kidney transplant donors and of one patient with liver cirrhosis. Interindividual variation in metabolite formation was considerable. Biphasic kinetics indicated the involvement of at least two distinct enzymatic activities. With use of a series of antisera that recognize different human cytochrome P450 isozymes, we were able to identify an enzyme of the P450III gene family as one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
132
0
3

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(139 citation statements)
references
References 0 publications
4
132
0
3
Order By: Relevance
“…Several human liver P450 from the subfamilies involved in xenobiotic oxidation have already been expressed in different systems, including recombinant simian virus 40 in COS cells and references therein; Romkes et al, 1991;Veronese et al, 1991), recombinant vaccinia viruses in human hepatoma Hep G2 cells (Aoyama et al, 1990a and1990b, and references therein) and recombinant plasmids in the yeast Succharomyces cerevisiae (Yasumori et al, 1989;Brian et al, 1989;Brian et al, 1990;Renaud et al, 1990;Eugster et al, 1990;Ching et al, 1991; Truan, G., Cullin, C., Reisdorf, P., Urban, P. and Pompon, D., unpublished results). P450 NF25 (CYP3A4) is important in pharmacology and toxicology, not only because it is probably the major form of human liver (Guengerich and Turvy, 1991) but also because it is involved in the metabolism of numerous widely used drugs such as nifedipine (Guengerich et al, 1986a), erythromycin and troleandomycin (Renaud et al, 1990 and references therein), quinidine (Guengerich et al, 1986b), cyclosporin A (Kronbach et al, 1988;Aoyama et al, 1989;Combalbert et al, 1989), 1 7a-ethynylestradiol (Guengerich, 1988), midazolam (Kronbach et al, 1989), lidocaine (Bargetzi et al, 1989;Imaoka et al, 1990), and diltiazem (Pichard et al, 1990). P450 NF25 was recently functionally expressed in S. cerevisiue (Renaud et al, 1990;Brian et al, 1990).…”
mentioning
confidence: 99%
“…Several human liver P450 from the subfamilies involved in xenobiotic oxidation have already been expressed in different systems, including recombinant simian virus 40 in COS cells and references therein; Romkes et al, 1991;Veronese et al, 1991), recombinant vaccinia viruses in human hepatoma Hep G2 cells (Aoyama et al, 1990a and1990b, and references therein) and recombinant plasmids in the yeast Succharomyces cerevisiae (Yasumori et al, 1989;Brian et al, 1989;Brian et al, 1990;Renaud et al, 1990;Eugster et al, 1990;Ching et al, 1991; Truan, G., Cullin, C., Reisdorf, P., Urban, P. and Pompon, D., unpublished results). P450 NF25 (CYP3A4) is important in pharmacology and toxicology, not only because it is probably the major form of human liver (Guengerich and Turvy, 1991) but also because it is involved in the metabolism of numerous widely used drugs such as nifedipine (Guengerich et al, 1986a), erythromycin and troleandomycin (Renaud et al, 1990 and references therein), quinidine (Guengerich et al, 1986b), cyclosporin A (Kronbach et al, 1988;Aoyama et al, 1989;Combalbert et al, 1989), 1 7a-ethynylestradiol (Guengerich, 1988), midazolam (Kronbach et al, 1989), lidocaine (Bargetzi et al, 1989;Imaoka et al, 1990), and diltiazem (Pichard et al, 1990). P450 NF25 was recently functionally expressed in S. cerevisiue (Renaud et al, 1990;Brian et al, 1990).…”
mentioning
confidence: 99%
“…Bargetzi et al (1989) have suggested that CYP3A4 contributes in a major way to the biotransformation of lidocaine to MEGX in humans. In this study, an antiserum directed against human CYP3A4 dose-dependently inhibited MEGX formation in human liver microsomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not clear what substrate concentration was used in this study. On the basis of the above in vitro studies (Bargetzi et al 1989;Imaoka et al 1990), it has been suggested that CYP3A4 is the major enzyme mediating lidocaine biotransformation in humans (Dollery 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have mg lidocaine irrespective of body weight. In study II, we studied all shown that the N-deethylation of lidocaine is catalyzed by our department's patients with histologically proven cirrhosis who the microsomal P-450 isoenzyme, III A4, 1 and that MEG-X were assigned a MEG-X test for clinical reasons. In addition, we formation depends on liver function.…”
mentioning
confidence: 99%